2021
DOI: 10.1111/jam.15117
|View full text |Cite
|
Sign up to set email alerts
|

Smart soil grouting using innovative urease‐producing bacteria and low cost materials

Abstract: Aims: Calcium carbonate is a biomineral whose precipitation could be mediated by ureolytic bacteria and contributes in strengthening of sandy soils. The type of bacteria and grade of reagents have significant influence on microbially induced calcite precipitation (MICP). In the present study, factorial experiments based on these two factors were designed to determine their potential on MICP process, taking into consideration the economic advantages while giving quality results as well. Methods and Results: For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Yeast extract is a protein-rich complex media that is conveniently used for bacterial cultivation. For MICPrelated studies, 20 g/L of laboratory-grade yeast extract is often used to cultivate S. pasteurii [7,8,14,21,23,[50][51][52]. However, some studies reported using 5 to 15 g/L of yeast extract [53][54][55][56].…”
Section: Bacterial Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Yeast extract is a protein-rich complex media that is conveniently used for bacterial cultivation. For MICPrelated studies, 20 g/L of laboratory-grade yeast extract is often used to cultivate S. pasteurii [7,8,14,21,23,[50][51][52]. However, some studies reported using 5 to 15 g/L of yeast extract [53][54][55][56].…”
Section: Bacterial Growth Performancementioning
confidence: 99%
“…It is Gram-positive, alkaliphilic, non-pathogenic, and has the propensity to generate endospores for survival in harsh environments [7]. The MICP has been demonstrated under various conditions (such as laboratory-scale, pilot-scale, and field-scale) as a potential sustainable technique for soil improvement and solidification [8][9][10][11], erosion control and prevention [12][13][14], and remediation of contaminants (such as copper, cadmium, and mercy) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, despite the numerous advances in MICP, most urease-producing bacteria utilised for various MICP applications are commercially procured from culture collection centres, which contribute to cost (Zomorodian et al 2019). According to the present global market price, it cost approximately US$402.0 to procure the original patent of S. pasteurii ATCC 11859, which suggests the low-cost advantage of utilizing indigenous ureolytic bacteria for various MICP applications (Ezzat & Ewida 2021). Further, the procured microorganisms are often associated with drawbacks regarding reduction in the population of the introduced bacteria into the soil due to competition, mechanical stress and predation arising from the non-adaptability of the organisms to the local environment (Burbank et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Those working with polyurethane grouting material can easily control the form and performance of a product by changing the type and share of its raw materials, so as to obtain the hard polyurethane foam [9,10]. Furthermore, the setting and curing time of polyurethane can be controlled comprehensively by adjusting the catalyst content and proportion of polyether polyol and isocyanate in polyurethane raw materials [11,12]. Reducing the curing time can realize rapid opening to traffic after road maintenance.…”
Section: Introductionmentioning
confidence: 99%